The contemporary instruments of teaching ten Qiraat Mutawatirat: A Comparative study on Arabic Qiraat institutions / Mohamad Anas Naji - Mohamad Anas , Naji (2018)
The science of Qiraat is considered as an important field because it is related to the words of Allah and second because of its direct impact on the meanings of the Quran. This research has been done due to its being important and second due to the lack of research concerned with this area of study. This is due to the lack of approaches as well as techniques of teaching. The aim of this research is to: 1- introduce both students and researchers who are interested in the science of Qiraat, to three Arabic institutions interested in teaching Qiraat, 2- to collect and select the most important ways and techniques of teaching Qiraat, 3- and to find solutions to simplify the way of teaching Qiraat. Then the researcher has presented his new program, which he produced to simplify and facilitate the teaching process of Qiraat. For the researcher to meet the objectives of the study, the inductive, comparative as well as experimental methods were used. The study has been done by first collecting data (the theoretical part) concerning the science of Qiraat and second by doing a case study (the experimental part) having been applied on three Arabic institutes:(Imam Al-Shatibi Institute in Saudi Arabia, the Preservation association of the Holy Quran in Jordan and the Institute of Dar Al-Itqan in Egypt). This has been done by first distributing questionnaires and then analysing and presenting the results of these questionnaires. Finally, Al-Muyassar program, that the researcher has produced, was presented and recommended to simplify and facilitate the fundamentals of the “Ten Qiraat”. The study has also found that the use of modern technology is extremely important in simplifying and facilitating the science of Qiraat in helping both students and teachers. The modern technological devices are very important instruments to help teachers, However, they cannot substitute them. These advance instruments have become a necessity, enabling us to combine the old and the modern methods of teaching Qiraat. The study finally concluded that Al-Muyassar Program has an obvious important effect in simplifying and facilitating the knowledge and understanding of the science of Qiraat. This is because this program has first made it easy for students and researchers to have an access for getting information about the science of Qiraat and second made it easy for students to remember the different ways of reciting and to compare between Qiraat.